Bidirectional association between NAFLD and gallstone disease: a systematic review and meta-analysis of observational studies. (4th March 2023) - Gu, Shengying; Hu, Shanshan; Wang, Shuowen; Qi, Chendong; Shi, Chenyang; Fan, Guorong
ABSTRACT: Background: Growing evidence indicates an association between NAFLD and gallstone disease (GD), while some does not support this. The aim of this meta-analysis was to evaluate the bidirectional association between NAFLD and GD. Research design and methods: Five electronic databases were searched from inception to May 2022. The association was analyzed based on the odds ratio (OR) and 95% confidence interval (CI) with Reviewer Manager 5.3. Results: Ten studies involving 284, 512 participants met the criteria for GD predicting the onset of NAFLD. GD patients had a higher incidence of NAFLD (OR:1.48, CI:1.32–1.65, p < 0.00001), especially the incidence of moderate-to-severe NAFLD (OR:1.63; CI:1.40–1.79), with females at a higher risk (OR: 1.84; CI: 1.48–2.29). The inverse association was explored in eight studies involving 326, 922 participants. The GD incidence in NAFLD patients was higher (OR:1.71, CI:1.63–1.79, p < 0.00001) and may increase due to female sex (OR: 4.18; CI: 1.21–14.37) and high BMI (OR: 1.80; CI: 1.36–2.56), compared with the non-NAFLD group. Besides, this bidirectional association was also confirmed in the Chinese population. Conclusions: The findings supported positive concurrent and bidirectional relationships between NAFLD and GD. Therefore, clinicians may alert the possibility of NAFLD in patients with GD and vice versa.